Exclusive Dealing and Vertical Integration in Interlocking Relationships - Volker Nocke; Patrick Rey (University of Mannheim, Department of Economics, 2014)
We develop a model of interlocking bilateral relationships between upstream firms (manufacturers)that produce differentiated goods and downstream firms (retailers) that compete imperfectly for consumers. Contract offers and acceptance decisions are private information to the contracting parties. We show that both exclusive dealing and vertical integration between a manufacturer and a retailer lead to vertical foreclosure, to the detriment of consumers and society. Finally, we show that firms have indeed an incentive to sign such contracts or to integrate vertically.
urn:nbn:de:bsz:180-madoc-370507
Keywords: L13; L42; D43; 330; vertical relations; exclusive dealing; vertical merger; foreclosure; bilateral contracting